EDUCATIONAL TECHNOLOGIES IN TEACHING AND LEARNING - Fayzullayeva Xushnura Zuxriddin qizi , (TADQIQOTLAR.UZ, 2023)
Abstract. The basic tendency of this paper is to analyze various views and experimental theories of educational technologies in teaching and learning as the increasing application. The article presents the main and brief content of all conflicting concepts and opinions in terms of myriad researchers’ theories and experiences on how to make the educational process effective and productive with the educational technologies.